COMPARISON OF RISK MANAGEMENT IN THE AVIATION AND AUTOMOTIVE INDUSTRIES - Agnieszka JĘDRUSIK (Humanities and Social Sciences)
The purpose of this article is to present the risk management process in the project management of two industries: aviation and automotive. The analysis was based on a comparison of the two approaches based on the risk matrix used. Risk management differs between industries, and it is up to the organization to choose the monitoring and methodology adapted to the specific sector. Risk management is an important aspect of the entire project life cycle and must be monitored throughout the project life cycle to protect not only the budget but all areas of the so-called "golden triangle." Of great importance is the organization's awareness that risk management is everyone’s responsibility, not just the project manager’s.